Randomized Questionnaire Based Case–Control Research Study on Evaluation of Sexual Function in Indian Patients Taking Oral Finasteride for Androgenetic Alopecia. Issue 4 (December 2015) - Narasimhalu, C.R.V.
Abstract Introduction Finasteride is one of the most common drugs used in androgenetic alopecia. The literature discusses the sexual side effects of the drug; however, in practice there is little evidence to support this. The aim of the present study was to investigate the sexual dysfunction in patients taking finasteride 1 mg for androgenetic alopecia. Methods A questionnaire, based on the International Index of Erectile Function, was given to approximately 586 patients with androgenetic alopecia who were being treated with finasteride 1 mg for an average of 16 weeks. These patients were compared to an age-related control group who were attending the Dermatology Out Patients Department for various other skin ailments not related to hair disorders. Results Statistical analysis of the results showed no significant difference in the scores between patients taking finasteride and the control group. Conclusion Analysis showed no significant difference in sex-related problems with that of patients taking finasteride and age matched controls, suggesting that sex-related issues are not a side effect of finasteride.